The realm of abstract worship - Svetlič, Rok (Annales. Series historia et sociologia, 2020)
The article thematises Hegel's account on Islam as found in his Lectures on the Philosophy of History. The discussion primarily examines the relationship between man, God/Absolute and the world in Islam, which, as Hegel demonstrates, is marked by irreducible abstractness. Two things emerge from abstractness, both the remarkable creativity of Islam (e.g. Poetry) and its inclination to violence, including its inability to build a solid political structure. To shed light on these limitations, the discussion refers on Hegel%s Science of Logic, where the condition for mutual interdependence of man, God/Absolute and the world are developed. In religious language, this interdependence articulates the concept of trinity, which makes it possible to overcome the shortcomings of the abstract approach.
Keywords: Georg Wilhelm Friedrich Hegel; islam; nasilje; philosophy of law; pravna filozofija; violence